Silicene Nanoribbon Tunnel Field Effect Transistor. (19th August 2016) - Fahad, Md S; Srivastava, Ashok; Sharma, Ashwani K; Mayberry, Clay; Mohsin, K M
Abstract : Stable room temperature operation of field effect transistor (FET) based on two-dimensional silicon (silicene) has recently been reported. Like graphene, silicene is a Dirac cone material. Silicene-based devices provide high off-state leakage current due to lack of a significant bandgap. However, quantum confined silicene nanoribbon (SiNR) shows observable bandgap which can be used for making switching transistors for digital integrated circuit design. Contrary to metal oxide semiconductor FET (MOSFET), tunnel field effect transistor (TFET) overcomes the physical limit of scaling of supply voltage. In this work, we present structure and characteristics of SiNR TFET using atomistic simulation based on self-consistent solution of 3D Poisson and Schrödinger equations within the non-equilibrium Green's function (NEGF) formalism. Performances are also compared with the International Technology Roadmap for Semiconductors (ITRS) projected high performance requirements of 2026 nMOSFETs.